MATERNAL DEATHS IN PUNJAB: A 3-YEAR AUDIT FROM A TERTIARY LEVEL GOVERNMENT INSTITUTE - Grover, Suparna; Sharma, Sujata; Sidana, Himanshi; Chhabra, Ajay (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study aims to recognize the most common causes and delays in maternal death. Methods: This is an observational study from Government Medical College Amritsar from the period December 2017 to November 2020 which included all cases of maternal death irrespective of gestational age and up to 42 days postpartum. Results: Maternal mortality ratio in our institute during 3-year study period (2018–2020) was 1081 per 100,000 live births. About 90.9% of the maternal deaths were unregistered emergency cases, 11.7% were brought dead, and 33.8% deaths took place within 24 h of admission. Direct obstetric causes were the most common causes of maternal death (49%), while indirect causes were responsible for 42.8% deaths. Hypertensive disorders and hemorrhage were responsible for almost one third cases and severe anemia was an aggravating factor in 31.5%. Maternal deaths were associated with type 1 delay in 57.6%, type 2 delay in 9% cases, and type 3 delay in 21.2%. Conclusion: Hypertensive disorders of pregnancy and obstetric hemorrhage continue to be the leading threats to maternal lives. Improvement in public health services and special campaigns focusing on prevention of viral hepatitis and other infectious diseases can be helpful in decreasing maternal death due to indirect causes. Need of the hour is quality intrapartum and emergency obstetric care at first referral units. Indirect causes of maternal death are a significant public health issue which needs to be addressed.